2014
DOI: 10.1165/rcmb.2013-0057oc
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression Level of the Cyclic Adenosine Monophosphate Response Element–Binding Protein Contributes to Lung Aging

Abstract: Lung aging is associated with morphological and physiological changes in which alterations in transcription factors, including the cyclic adenosine monophosphate response element-binding protein (CREB), could play a role. We studied CREB in lung tissue from mice at different ages and in response to known age-related factors (e.g., cellular senescence and matrix modifications with advanced glycation end-products [AGEs]). Our study shows that protein but not mRNA levels of CREB are reduced in the lungs of old mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…None of these factors could explain the difference for RAB27A locus effects between children and adults because the genetic association signal was mainly observed in non-smoker, non-asthmatic or non-atopic individuals. Instead, the specific effect of the RAB27A polymorphism on FeNO levels in adults might reflect a strong gene by age interaction, which would be consistent with several lines of evidence implicating RAB27A in age-related changes of bronchial airways [27, 28]. In that light, it is possible that the adult-specific association could be related to ageing process or other factors throughout life that might influence FeNO levels.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…None of these factors could explain the difference for RAB27A locus effects between children and adults because the genetic association signal was mainly observed in non-smoker, non-asthmatic or non-atopic individuals. Instead, the specific effect of the RAB27A polymorphism on FeNO levels in adults might reflect a strong gene by age interaction, which would be consistent with several lines of evidence implicating RAB27A in age-related changes of bronchial airways [27, 28]. In that light, it is possible that the adult-specific association could be related to ageing process or other factors throughout life that might influence FeNO levels.…”
Section: Discussionsupporting
confidence: 72%
“…Pulmonary epithelium atrophy has been described in lungs of double knockout mice (Rab27a and Rab27b), and interestingly these morphologic changes were observed in aged mice only (over 12–18 months) [27]. Moreover, a reduced expression of RAB27A was found in old mouse lung tissue (25–31 months), as well as in human senescent lung fibroblasts and lung epithelial cells [28]. These observations are in agreement with the absence of association signal between FeNO levels and SNPs at the RAB27A locus in the EAGLE children cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…CREB expression and activation in lungs are impaired with age, as they were reduced in adult compared to young mice, and further decreased in old vs. adult animals. 39 As COPD is considered a disease of accelerated lung aging, 40,41 our findings imply that any such impairment may also conceivably contribute to COPD-associated GRα downregulation.…”
Section: Discussionmentioning
confidence: 75%
“…CREB1, CAMP responsive element binding protein 1, is a protein that binds the cAMP response element and regulates transcription. Its expression and function can modulate oxidative stress-induced senescence in granulosa cells by reducing the mitochondrial function [ 85 ] and CREB signaling has been related to lung and brain aging [ 86 , 87 ]. Finally, EIF5A2 encoding for the Eukaryotic Initiation Factor 5A2, plays a key role in the regulation of protein translation, and it has been reported that, in transgenic mice, its overexpression enhances the aging process [ 88 ].…”
Section: Discussionmentioning
confidence: 99%